Influence of Experiential Value on the Loyalty in Travel Websites - Dey, VetoDey; S, Vasantha (International Journal of Supply Chain Management, 2018)
In the present scenario searching information through online and booking tickets through travel websites supports the digitalization initiatives of our Government. In the digital world customers are able to decide, how, when and what they want to see and search by switching from one website to other. As numerous number of website increases every minute, sometime it is very difficult to distinguish. The presence of too many tour and travel websites created complications for the marketers and increase their competence level with the others. In view of the increasing importance of the different websites in tourism the managers of the websites should understand that e-shopping experience must deliver some value if they want to turn website browsers into bookers. The objective of the study is to empirically test the relationship between experiential value and loyalty.   Key words: Customers Experiential value, Loyalty, Travel website